Metode Pengajaran Bahasa Arab Kepada Penutur Asing dalam Buku Metode Pengajaran Bahasa Arab Dalam Bahasa Lain Karya Dr. Abdul Aziz bin Ibrahim Al-Asili dan Analisisnya - Isyraq Suleiman Hasyim Rumanah (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2023)
It is known that foreign language learners must face difficulties in learning the language, especially in students who have not been able to pronounce the language and are not familiar with it starting from differences and similarities found in the language such as sound or writing or structuring language for the language of the student in learning the language, especially learning Arabic for beginners in Arabic is not easy. Dr. Abdul Aziz bin Ibrahim Al-Osaili, author of books related to the Arabic language from the illuminations of Arabic language teachers, as well as methods of teaching it and others. The researcher aimed to analyze the methods of teaching Arabic to non-native speakers in his book Methods of Teaching Arabic in Other Languages. To reach the knowledge of this research, the researcher used the descriptive analytical approach by analyzing the methods of teaching Arabic to non-native speakers in his book Methods of Teaching Arabic in Other Languages. One of the results of the research is that it was found that the methods of teaching Arabic to non-native speakers in this book according to how the teacher uses it.